Anti‐tumoral effects of low molecular weight heparins: A focus on the treatment of esophageal cancer. Issue 10 (9th May 2018) - Javadinia, Seyed Alireza; Gholami, Arezoo; Joudi Mashhad, Mona; Ferns, Gordon A.; Shahidsales, Soodabeh; Avan, Amir; Kermani, Ali Taghizadeh
Abstract : Esophageal cancer is one of the most prevalent types of cancer globally. With current treatment options, the survival is poor, and there are ongoing efforts to find new and more efficient therapeutic approaches. There are several reports on the anti‐tumoral effects of low‐molecular‐weight heparins (LMWH). We have assessed the possible survival benefits and underlying mechanisms of LMWHs in malignancies with a focus on esophageal cancer. We conclude that the effects of LMWHs on survival of cancer patients is probably due to a combination of direct anti‐tumoral, anti‐angiogenic, and immunomodulatory effects and indirect effects on the coagulation system. Abstract : LMWHs have potential effects on survival of cancer patients that is probably due to a combination of direct anti‐tumoral, antiangiogenic, and immunomodulatory effects and indirect effects on the coagulation system.